The Numerical Study of Multi-Stage Cold Forming Process for the Manufacture of SCM435 Alloy Steel Flange Nuts - Yang, Chih-Cheng; Peng, Jun-Shuo; Duan, Yan-Siang; Sung, Chen-Lun (European Journal of Applied Sciences, 2025)
In this study, a multi-stage cold forming process for flange nut manufacturing using SCM435 alloy steel is numerically investigated. The cold forming process through five stages includes flattening along with centering, upsetting a hexagonal shape along with backward extrusion, upsetting a flange along with backward extrusion, and piercing. The numerical study of cold forming is conducted using the finite element code of DEFORM-3D. The formability of the workpiece is studied, such as the influence on forming force responses, maximum forming forces, effective stress and strain distributions and metal flow pattern. In the five-stage forming process, for the forming stages of upsetting along with backward extrusion and piercing, due to large deformation, the effective stresses in the workpiece are significantly high, and so the effective strains. The flow line distributions are also very complex, where the flow lines in the piercing region around the inner wall of the hole are severely bent, highly compacted, and eventually fractured. For the maximum axial forming force, the first stage of flattening and centering for backward extrusion is 368.5 kN, which is the largest among the five stages, while the forming energy of 183.3 J is the smallest due to shorter acted axial forming stroke. For the forming energy, the second stage, which the workpiece is upset into a hexagonal shape along with backward extruded into a cavity; and the third stage, which the workpiece is upset into a flange along with backward extruded into a cavity, are respectively 456.7 J and 455.7 J that are very close, which are the first and second largest forming energy among the five stages due to longer acted axial forming strokes. The total maximum axial forming force from the first to the last stages is 1,061.4 kN and the total forming energy is about 1.637 kJ.